Variations of oral anatomy and common oral lesions - Paulo Ricardo Martins Souza; Letícia Dupont; Gabriela Mosena; Manuela Lima Dantas; Lucas Abascal Bulcão (Sociedade Brasileira de Dermatologia, 2024)
Abstract Several topics related to the oral cavity are briefly addressed in this article, from anatomical variations that, when recognized, avoid unnecessary investigations, to diseases that affect exclusively the mouth, mucocutaneous diseases, as well as oral manifestations of systemic diseases. A complete clinical examination comprises the examination of the mouth, and this approach facilitates clinical practice, shortening the path to diagnosis in the outpatient clinic as well as with in-hospital patients. The objective of this article is to encourage the examination of the oral cavity as a useful tool in medical practice, helping to recognize diseases in this location.